Cladding process using gas metal arc welding as a heat source and 308L stainless steel wire as feedstock - Asri, Nur Fawwaz (2014)
Cladding technology in parts of manufacturing and repairing has been applied in many areas such as aerospace and automotive industries. One of the purposes of this technology is to prevent metallic surface from corrosion and wear. In order to reduce cost in tools and dies, layer-by-layer deposition technique in cladding process was formed by Gas Metal Arc Welding (GMAW) as a heat source. Stainless steel wire of 308L was used as a feedstock in which deposited on carbon steel substrate. The stainless steel wire was used to build the overlapped cladding for its known potential advantages. The 308L stainless steel clad was deposited directly by using a GMAW robotic welding to give a pore and crack free structure. The study was divided into two parts namely the investigation for stainless steel single bead clad and overlapped cladding (30% and 50% overlapped). The microstructure and microhardness behaviour of the 308L stainless steel structure was studied and solidification of 308L stainless steel during cladding process leads to dendritic formations which influence mechanical properties of the clad structure. Heat flow was studied to understand microstructure and microhardness variations of the clad material. The study also analysed corrosion behaviour of 308L stainless steel clad after cladding process. Design of Experiment (DOE) was employed in generated process parameter using Response Surface Methodology (RSM) method. Furthermore, the microstructural evolutions of 308L stainless steel cladding were investigated and the clad deposits were characterised by optical microscope, elemental mapping, Energy Dispersive X-ray (EDX), Vickers microhardness testing and electrochemical analysis. Results from the microstructural and microhardness properties was relate to the heat flow from the cladding process. The corrosion behaviour using Tafel extrapolation method was analysed in measuring the corrosion level of 308L stainless steel. Finding results indicated sample 12 (19.5V, 200 A and 35 cm/min) shows low corrosion rate behavior for 30% overlapped